Analyzing the Impact of YouTube Watch Time on Higher Education Institution Promotions and Admissions - Akbari, Deni Adha; Rochaety, Eti (Technium Social Sciences Journal, 2023)
This study analyzes the impact of YouTube watch time on higher education institution promotions and admissions, using data from the UhamkaTV YouTube channel from January 1 to December 31, 2022. The analysis focused on the watch time (in hours) and watch time percentage for the top five videos on the channel during the specified period. The results indicate that the video "UHAMKA Online Registration 2022" garnered the highest watch time of 5,726.9 hours, accounting for 62.8% of the total watch time. This video’s high watch time percentage suggests that content related to the online registration process is highly relevant and engaging for prospective students. The other videos had significantly lower watch time percentages, meaning their promotional impact may not be as significant as the first-ranked video. These findings suggest that YouTube watch time can dramatically impact the promotion and admissions of higher education institutions. Higher education institutions can leverage YouTube to provide relevant and engaging content related to admissions and academic programs to potential students. This study provides insights that can inform the development of effective YouTube marketing strategies for higher education institutions.